NILAI-NILAI PENDIDIKAN DALAM PERMAINAN ANSAMBEL RECORDER - Tiwi Hartati; Wimbrayardi Wimbrayardi; Ardipal Ardipal (SENDRATASIK UNP, 2013)
Abstract This article aims to reveal and explain the value of education in game recorder ensemble in MTsN Tanjung Raya. This research is a qualitative descriptive method. Data obtained by direct observation, interviews, library research, and documentation. Data were analyzed with phenomenological techniques. The results showed, that in the game there ensemble educational aspects and attitudes for students MTsN Tanjung Raya. With the recorder ensemble extracurricular learning, then the recorder ensemble play can produce benefits to educate the attitude and behavior of students in collaboration, compliance and obedience, responsibility, discipline, and being consistent in doing and acting.